Manufacturing Process of CAR-T Therapy and Assessment of the Optimization Potential - Wang, Jiayi; Wang, Kaixin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
One ground-breaking novel treatment that is being utilized extensively in the field of cancer treatment is chimeric antigen receptor (CAR)-T cell therapy. Three axes are used by CAR-T cells to promote tumor killing: Targeting the antigen-positive fraction is the Perforin and Granzyme axis; Targeting the antigen-negative fraction is the Fas and FasL axis; and Cytokine release is focused on the Stromal cell. As a result of this technology's widespread use, its benefits and applications have increased; yet, drawbacks and toxicities have also been discovered. The wide range of uses for this cutting-edge technology has resulted in an increase in its advantages and uses. Alongside these benefits, studies have also discovered negative effects and toxicities related to its usage. This work analyzes the complexities of the specialized immunotherapy mechanism, the difficulties associated with this technology, toxicity issues, and future directions in the treatment of CAR-T cells. Its potential to completely transform the way cancer is treated is becoming more and more evident as the medical community works to understand the intricacies of this innovative therapy.